Post-COVID-19 rehabilitation – a Polish pilot program - Jan Szczegielniak (Nofer Institute of Occupational Medicine, 2021)
The current spread of SARS-CoV-2 indicates a long-term fight against the widespread and exponential increase in morbidity and mortality across the globe. A variety of non-pharmacological strategies to mitigate and suppress virus transmission have been investigated and introduced. Currently, emerging studies focus mostly on the management of hospital-treated patients in the acute phase of the disease, including the legitimacy of using physiotherapeutic procedures. However, current literature lacks guidelines for rehabilitation related to maintaining continuity and universality of the therapy after the end of the acute phase of the disease and discharge from hospital. The authors suggest implementing an immediate rehabilitation program in post-infection patients as data from previous epidemics of respiratory-related viral diseases shows that COVID-19 survivors should be expected to have impaired lung ventilation function, and reduced exercise tolerance and muscular weakness, and prolonged return to work and participation. It should be assumed that only the introduction of immediate recommendations for the implementation of rehabilitation procedures based on simple and well-known tests, as well as their obligatory regime, can contribute to the reduction of respiratory disability leading, in a short time, to infections recurrence and, in the long run, to a lower quality of life and socioeconomic burden on the population. This article presents a respiratory rehabilitation program for COVID-19 survivors, recommended by the Polish Society of Physiotherapy. This program was approved by the Polish Minister of Health and implemented as a pilot program at the Hospital of the Ministry of the Interior and Administration in Głuchołazy, Poland. Med Pr. 2021;72(5):611–6